The wolf gift : a novel - Rice, Anne, 1941- (New York : Alfred A. Knopf, 2012)
A young reporter on assignment is attacked and bitten by an unknown beast in rural Northern California and begins a terrifying but seductive transformation into a being with a dual nature, both man and wolf.
English Language & Literature.
Keywords: Werewolves -- Fiction; Identity (Psychology) -- Fiction; Paranormal fiction; Horror fiction